"Divine Justice and State Law for Corruptors: A Review of Surah Thaha Verses 124–128 in the Asset Confiscation Law" - Uus Husni Khoiri; Syarif Hidayat; Muhamad Qomarudin; Tiara Safitri (al-Afkar, Journal For Islamic Studies, 2026)
Corruption is an extraordinary crime that harms society. A draft Asset Confiscation Bill (RUU) has been proposed to confiscate assets obtained from corruption without waiting for a final criminal verdict, but has not been passed due to various obstacles. This study analyzes the relationship between asset confiscation in Islamic law and the interpretation of QS. Thaha: 124–128, specifically the meaning of ma'isyatan dhankan (narrow life) as a consequence for perpetrators of injustice. This study uses a qualitative method with a thematic interpretation approach and normative analysis of Islamic law and Indonesian regulations. The results indicate that asset confiscation is in line with the principle of Islamic justice, where illicit assets must be returned to the community. This study recommends accelerating the ratification of the Asset Confiscation Bill and wider dissemination for its effective implementation in eradicating corruption.